Development of semi refined carrageenan/glycerol/a-tocopherol reinforced with cellulose nanofiber for active packaging application - Wan Amnin, Wan Yahaya (2020)
Active packaging incorporated with natural antioxidant is a promising technology to extend shelf life of perishable food. However, biopolymers such as semi-refined carrageenan SRC alone does not form films with adequate mechanical properties which limit their potential as packaging film for food protection. The application of reinforcing fillers to biopolymers has proven effective in improving their thermal, mechanical, and barrier properties. This study aims to produce the bioactive edible film made semi refined carrageenan (SRC) plasticized with glycerol (G) enhanced with cellulose nanofibers (CNF) as reinforcing agent incorporated α-tocopherol (Tp) to enhance lipid oxidative stability of meat patties. Semi-refined carrageenan film reinforced cellulose nanofibers plasticized with glycerol and incorporated α-tocopherol were produce using casting method. The concentration of cellulose nanofibers was determined to enhance active films with mechanical and physical properties. The films produced have distinguished for their mechanical and physical characterization. Thereafter, the effectiveness of semi-refined carrageenan/glycerol/α-tocopherol as active packaging film to prolong the shelf life of meat patties were evaluated. This study exhibited that the addition of cellulose nanofibers were improved the physical and mechanical properties compare to control film (semi-refined carrageenan without the addition of glycerol, cellulose nanofibers and α-tocopherol). This can be shown at the tensile strength and elongation at break, which were improved with the increase in concentration (2%, 5%, 7% and 10% [v/v]) cellulose nanofibers (p<0.05) with value range of tensile strength (56.83-66.79 Mpa) and elongation at break (17.23-46.54%). However, increasing the concentration 13% (v/v) cellulose nanofibers had reduced the tensile strength (44.98 Mpa) and elongation at break significantly (32.93%) (p<0.05). When compared to the control film, the opacity value of semi-refined carrageenan reinforced cellulose nanofibers attribute lower opacity (4.09-4.73 mm-1). On the other hand, the film solubility and moisture content were improved significantly by increasing concentration of cellulose nanofibers. The thermal stability was improved by adding CNF to the film. In spite of this, the release antioxidant of the active films to the food simulant (95%) ethanol was calculated during 31 days of storage using total phenolic content and DPPH scavenging activity assays. The extended release of antioxidant into food simulant was from 31-day storage with total phenolic content value of 250.40-362.67 mg GA/L sample and 81.07-86.59% inhibition for DPPH assay. Moreover, the development of lipid oxidation in the meat patties wrapped with antioxidant films was delayed during storage with a final value of 0.68-0.37 mg of malondialdehyde/kg sample. Overall, active film reinforced with 10% (v/v) cellulose nanofibers improves mechanical properties of the film cellulose in terms of tensile strength and elongation at break. Hence, the new formulation of semi refined carrageenan (SRC) plasticized with glycerol (G) enhanced with cellulose nanofibers (CNF) as reinforcing agent incorporated with α-tocopherol (Tp) could be an promising option as active packaging to improve food safety and quality of the meat under refrigerated environment.